2016 European Conference on Networks and Communications (EuCNC) 2016
DOI: 10.1109/eucnc.2016.7561042
|View full text |Cite
|
Sign up to set email alerts
|

Fronthaul performance demonstration in a WDM-PON-based convergent network

Abstract: Cloud Radio Access Network (C-RAN) and Fixed Mobile Convergence (FMC) receive a lot of attention recently because of the cost decrease and the performance improvement that they represent for telecommunications' operators. In this paper, a fixed/mobile convergent architecture is introduced based on the integration of fronthaul links with fiber access infrastructure and central office assets. Tests have been performed on a wireline business service and an LTE fronthaul link measuring performances in terms of Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The PON based system is a practical solution because it is cost effective and is readily available for the transportation of fronthaul date in a small cell scenario [16,17]. Since it uses fiber optics as medium of transmission, it can carry the huge fronthaul data of CPRI in an ultra-dense small cell network.…”
Section: Pon Based Systemmentioning
confidence: 99%
“…The PON based system is a practical solution because it is cost effective and is readily available for the transportation of fronthaul date in a small cell scenario [16,17]. Since it uses fiber optics as medium of transmission, it can carry the huge fronthaul data of CPRI in an ultra-dense small cell network.…”
Section: Pon Based Systemmentioning
confidence: 99%
“…[25] verifies the compatibility of a self-seeded DWDM solution with the most critical fronthaul requirements with regard of the data rate, the bit error rate, the jitter, the round trip delay and the radio frequency accuracy budget. In [26], experiments were performed on a fronthaul link measuring performances in terms of Ethernet frame loss on the CPRI data transport in a wavelength division multiplexing-passive optical network (WDM-PON)-based fronthaul networks. Beside 100 Gb/s coherent WDM-PON system can also be applied in mobile fronthaul [27].…”
Section: High-bandwidth Provisionmentioning
confidence: 99%
“…Currently commercial systems are only available for the 2.45 Gb/s line rate (CPRI option 3). In recent measurements (compare Table 1) the compliance of a WDM-PON system with the CPRI standard has been evaluated at different line rates [11]. It has been shown that for CPRI options 3 (2.45 Gb/s) and 5 (4.91 Gb/s) the maximum jitter specification is fulfilled.…”
Section: Structural Convergencementioning
confidence: 99%